2012
DOI: 10.1016/j.drugalcdep.2012.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of adolescent alcohol use after brief treatment in an Emergency Department

Abstract: Objective The primary aim of this study was to identify distinct classes of trajectories of adolescent substance use following a brief motivational interviewing (MI) intervention in an Emergency Department (ED). The secondary aim was to identify predictors of class membership. Methods Latent growth mixture modeling was used with 177 adolescents who participated in two randomized clinical trials evaluating MI for an alcohol-related event. Results Three classes were identified: (1) moderate use, decreasers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Yet, only a few have examined adolescent addiction treatment mechanisms and outcomes for Hispanic youth (e.g., Becker et al, 2012; Clair et al, 2013). This is important because while some argue that MI is ideally suited for Hispanic youth, it is equally possible that the approach of MI may be a poor fit (Feldstein Ewing, Wray, Mead, & Adams, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, only a few have examined adolescent addiction treatment mechanisms and outcomes for Hispanic youth (e.g., Becker et al, 2012; Clair et al, 2013). This is important because while some argue that MI is ideally suited for Hispanic youth, it is equally possible that the approach of MI may be a poor fit (Feldstein Ewing, Wray, Mead, & Adams, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a case-control study examining depression and alcohol use among adolescents recruited from either an urban ED or community site, adolescents receiving ED services were significantly more likely to report both increased alcohol use disorders and major depression as compared to the community sample (Kelly et al, 2003). In another study, Becker et al (2012) examined the impact of depression on drinking trajectories after receiving urban ED services and found that baseline depressive symptoms significantly impacted drinking frequency over the following 12 months. Additionally, studies examining higher-risk subgroups of ED patients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the drinking trajectories of adolescents immediately following the receipt of alcohol interventions, and even less is known about adolescents receiving brief interventions. In fact, to date, only one study has examined the drinking trajectories of adolescents after they received a brief, evidence-based intervention (Becker et al, 2012), and only two have examined the trajectories of adolescents on a month-by-month basis over the course of 1 year following alcohol or other drug treatment (Chung et al, 2004(Chung et al, , 2005. In the Becker et al (2012) study, data from 3-, 6-, and 12-month follow-up interviews were examined, and three classes of response were identified: moderate users who decreased use over time, heavy users who decreased use, and heavy users who sustained use following a brief intervention in an emergency department.…”
mentioning
confidence: 99%
“…Rigorous Timeline Followback (TLFB) methods were used to obtain daily estimates of alcohol use behaviors, which were then aggregated at the monthly level to examine trajectories. Monthly data, gathered using TLFB methods, provide for a much more granular and thorough examination than previous longitudinal work (e.g., Becker et al, 2012). This granularity provides for the identification of potential targets of intervention in future work.…”
mentioning
confidence: 99%